1976
DOI: 10.1104/pp.58.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Patterns of Photosynthesis and Respiration by Stems of Populus tremuloides Michx.

Abstract: The photosynthetic and respiratory rates of 5-to 7-year-old aspen stems (Populus tremuloides Michx.) were monitored in the field for 1 year to determine the seasonal patterns. The stem was not capable of net photosynthesis, but the respiratory CO2 loss from the stem was reduced by 0 to 100% depending on the time of year and the level of illummination as a result of bark photosynthesis. The monthly dark respiratory rate ranged from 0.24 mg COdm2 hr in January to a maximum 7.4 mg COdm2-hr in June. Individual mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
36
1
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 7 publications
5
36
1
1
Order By: Relevance
“…58. 1976 The excess of respiration over photosynthesis combined with high phellem diffusion resistance increased the internal stem CO2 concentration in stem gas during summer months to 5 to 15% (2,4,21). We would.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58. 1976 The excess of respiration over photosynthesis combined with high phellem diffusion resistance increased the internal stem CO2 concentration in stem gas during summer months to 5 to 15% (2,4,21). We would.…”
Section: Discussionmentioning
confidence: 99%
“…(aspen) bark CO2 exchange. Chl analysis of the green bark layer has revealed that on a surface area basis, the Chl concentration is similar to the Chl content of aspen leaves (3,14,17), making it a promising organism for this study of both physiological and ecological aspects of bark photosynthesis (4 Photosynthetic and respiratory CO, exchange rates were measured using a 30-cm, water-cooled, acrylic plastic cuvette consisting of two halves that could be placed around the stem and sealed with no apparent injury to the stem (5). To reduce water, CO2, and heat gradients within the cuvette, an air recirculation system was used with the cooling coils submerged in water or a water-ethanol mixture depending on the operating temperature (5).…”
mentioning
confidence: 99%
“…Photosynthesis in woody stems is best known in the bark of quaking aspen, Populus tremuloides 17,19,20, 22). Net CO2 assimilation by illuminated aspen bark has never been reported, but photosynthesis (reduction of CO2 release rates on illuminated) is known to occur over a wide range of temperatures and during all seasons of the year (9,10,17).…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis in woody stems is best known in the bark of quaking aspen, Populus tremuloides 17,19,20, 22). Net CO2 assimilation by illuminated aspen bark has never been reported, but photosynthesis (reduction of CO2 release rates on illuminated) is known to occur over a wide range of temperatures and during all seasons of the year (9,10,17).Although the photosynthetic performance of older stem tissues is reasonably well studied, little is known about growing internodes of woody species. Because young, growing stems of woody species intergrade from an entirely primary tissue system to a predominately secondary tissue system, the photosynthetic and respiratory rates of juvenile aspen stem could vary with the age and developmental stage of the internodes.…”
mentioning
confidence: 99%
“…The IR gas analyzer is the instrument most commonly used to measure CO2 concentrations. Flow-through systems which monitor CO2 exchange of plants or plant parts enclosed in a chamber usually depend on the detection of a 10 to 30 pl C02/1 concentration differential between input and exhaust air (3,(7)(8)(9)12). The CO2 differentials can be related to net photosynthesis or respiration.…”
mentioning
confidence: 99%